Combination of Transcranial Magnetic Stimulation with Electromyography and Electroencephalography: Application in Diagnosis of Neuropsychiatric Disorders - Farzan, Faranak; Barr, Mera S.; Fitzgerald, Paul B.; Daskalakis, Zafiris J. (IntechOpen, 2012)
None